Soft and Hard Skills in Accounting Field-Empiric Results and Implication for the Accountancy Profession - Cernușca, Lucian (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The main objective of the research is to study the perception of students in accounting profile within the "AurelVlaicu" University of Arad in comparison with the employers’ perception of the hard and soft skills needed in view of the accounting graduates’ access on the labour force market. The target group has been asked to express its opinion on the skills required to candidates to access the jobs in order to penetrate thelabour force market in the field of accounting. In order to achieve this objective, an empirical study based on a cross-cutting descriptive research has been carried out, the method chosen is the survey based on a questionnaire. The target group consists of 250 students majoring in accounting within "AurelVlaicu" University of Arad, as well as from 300 professional accountants who are members of CECCAR (The Body o Experts and Chartered Accountants of Romania). The case study concluded that a large part of the interviewed accountants have considered that employers would be increasingly interested in hiring young graduates in accounting that hold strong soft skills, being also willing to subsequently invest in trainings to develop their hard skills that they need daily in the chosen job. In order to succeed and perform in the field in which they will work, accounting students (future accounting professionals) must hold a set of powerful soft skills to complete the hard skills acquired and tested during the academic studies. The target group interviewed in the case study considers it would be useful the accounting students to participate in internships, scientific sessions, Erasmus scholarships, voluntary actions, Work and Travel Programs, teambuilding programs, national and international projects, summer schools, student scientific clubs to develop hard and soft skills during the university studies. In order to generate sustainable organisational success, future professionals who will be working in the field of accountancy will have to possess both hard skills and soft skills to be able to contribute in this way to the success of the organization they will be part of and the accounting profession will gain.